The Role of Human Resource Development and Motivational Factors in Improving Employee Performance at PT Aerofood Indonesia, Surabaya Unit - Fadhlulrrhahman Surya Prayoga; Achmad Sholihin (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of Human Resource Development (HR) and Motivational Factors on Employee Performance at PT Aerofood Indonesia Unit Surabaya. This study uses a quantitative method with a survey approach. Data collection was carried out through the distribution of questionnaires to 41 respondents who were selected using the simple random sampling technique. Data were analyzed using validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and determination coefficient (R²) test with the help of the SPSS program. The results of the study showed that the HR Development variable had a positive and significant effect on Employee Performance with a t-count value of 5.718 and a significance value of 0.000 < 0.05. The Motivation Factor variable also had a positive and significant effect on Employee Performance with a t-count value of 2.970 and a significance value of 0.005 < 0.05. Simultaneously, the variables of Human Resources Development and Motivation Factors had a positive and significant effect on Employee Performance with an F-count value of 215.888 and a significance value of 0.000 < 0.05. In addition, the determination coefficient (R²) value of 0.919 indicates that 91.9% of the variation in Employee Performance can be explained by the variables of Human Resources Development and Motivation Factors, while the remaining 8.1% is influenced by other factors outside the study. The results of this research are expected to be considered for companies in improving the quality of human resource development and work motivation to achieve more optimal employee performance.